Androstane‐Type Steroidal Glycoside from the Roots of Asparagus curillusBuch.‐Ham. ex Roxb. Issue 3 (13th March 2013) - Semwal, Deepak Kumar; Semwal, Ruchi Badoni; Singh, Gurjaspreet
Abstract The novel androstane‐type steroidal glycoside 1 was isolated from the roots of Asparagus curillusBuch.‐Ham. ex Roxb. Its structure was elucidated as (2α, 3β, 5α, 17β)‐17‐(1‐methoxyethoxy)‐17‐methylandrostane‐2, 3‐diol 3‐(β‐D‐digitoxopyranoside) by means of chemical and advanced spectral analysis.